Role of GSH in the modulation of NOS-2 expression in the weaned mammary gland. (26th October 2005) - Zaragozá, R.; García-Trevijano, E.R.; Miralles, V.J.; Mata, M.; García, C.; Carmena, R.; Barber, T.; Pallardó, F.V.; Torres, L.; Viña, J.R.
Abstract : GSH delivery to the lactating mammary gland is essential for the maintenance of lactation as its decrease leads to apoptosis and involution of the mammary gland. In fact, it has already been demonstrated that some of the changes in gene expression found in the lactating mammary gland after forced weaning are reproduced in rats treated with buthionine sulphoximine to deplete GSH levels. An oligonucleotide microarray experiment would give us a better knowledge of the mRNA expression patterns during lactation and after weaning and the possible functions of GSH in the modulation of these events.